Financial Knowledge and Social Influence on Generation Z Intention to Invest: The Mediating Role of Financial Attitude and Literacy - Eristy Minda Utami; Gusni Gusni; Reva Yuliani; Gordana Pesakovic (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2025)
The growing impact of technology has attracted a greater number of people, especially Generation Z, to financial markets. Enhancing financial literacy and attitudes is essential for promoting informed investing choices. This research analyzes the impact of financial knowledge and social influence on Generation Z's investment aspirations, while accounting for the mediating functions of financial literacy and attitude. This research seeks to elucidate the mediating role of financial literacy and attitude in the interaction among financial knowledge, social influence, and investment intentions. A survey methodology was used with a sample size of 200 students enrolled in capital market courses at Widyatama University. The results demonstrate that financial knowledge and attitudes substantially affect investing intentions among Generation Z. Furthermore, financial acumen and social influence indirectly impact investing intentions via these mediating variables. These findings emphasize the need of thorough financial education to develop superior investing strategies among young individuals. Theoretical implications indicate that augmenting financial awareness and attitudes may significantly enhance investment decision-making among Generation Z.